PERBEDAAN KOLAGEN IV DI KERUSAKAN HATI DAN INFEKSI HEPATITIS C PASIEN TALASEMIA DENGAN KELEBIHAN ZAT BESI (Diferrence of Collagen IV in Liver Damage and Hepatitis C Infection in Iron Overload Thalassemia Patients) - Nuri Dyah Indrasari; Ina Susianti Timan; Pustika Amalia (Indonesian Association of Clinical Pathologist and Medical laboratory, 2015)
Thalassemia patients who receive repeated blood transfusions are at risk of iron overload and hepatitis C infection. Iron overload cancause iron deposit in many organs, including the liver. Iron deposits in the liver and hepatitis C infection can cause chronic inflammationof the liver and induce hepatic stellate cells to produce Extra Cellular Matrix (ECM) causing liver fibrosis. Laboratory diagnosis of liverfibrosis is based on direct and indirect markers. Collagen IV is a direct marker reflecting ECM degradation in liver fibrosis. AlanineTransaminase (ALT), Aspartate Transaminase (AST) and AST/ALT ratio are indirect markers reflecting liver cell damage due to liverfibrosis. The aim of this study was to investigate the difference of Collagen IV in liver damage and hepatitis C infection in thalassemiapatients with iron overload. Collagen IV was measured using ELISA, while ALT and AST were measured by enzymatic colorimetric assay.Fifty eight thalassemia patients with iron overload, 29 with hepatitis C and 29 without hepatitis C were studied. This study showed nosignificant difference in Collagen IV level, ALT, AST activity and AST/ALT ratio between subjects with and without hepatitis C(p 0.131,0.243, 0.256 and 0.726) and no significant correlation was found between collagen IV level and ALT activity, and between collagen IVand AST/ALT ratio (p 0.160 and 0.509). These findings indicate that Collagen IV showed no correlation with liver damage and hepatitisC infection in thalassemia patients with iron overload.